Governing Gaza : Bureaucracy, Authority, and the Work of Rule, 1917–1967 - Feldman, Ilana, 1969- (Book collections on Project MUSE., 2008)
An investigation into how government persists under even the most untenable conditions, based on an analysis of government in Gaza between 1917 and 1967.